Measurement of the acoustical performance of traditional vernacular mosques in Malaysia - Che Din, Nazli; Abd Jalil, Nurul Amira; Ahmad, Yahaya; Othman, Rosniza; Otsuru, Toru (2013)
Mosques are worship places used for activities performed by Muslim e.g. prayer, speech and Quran recitations. All activities in the mosques are important acoustical interests for satisfactory speech intelligibility i.e. verbal communication. Unfortunately, recent architectural styles or restoration works were given very little attention about acoustical considerations. In this research, the acoustical performance of five selected traditional vernacular mosques in Malaysia, built between 1728 – 1830, have been investigated as a preliminary study. The acoustic parameters such as reverberation time (RT), clarity (C50) and speech transmission index (STI) were measured. Measurement of the influence of the operating facilities in the mosques on their acoustic quality was also carried out. The PC-based measuring system (dBBati32) with sound level meter (01dB Solo Metravib) as analyzer was utilized. Data collected reveals initial findings that the operating facilities in the mosques resulting higher rating of noise criteria which is reducing the performance of speech intelligibility.